Biodiversity and five novel species of myxozoan parasites in Barbonymus spp. (Cyprinidae, Cypriniformes) from Malaysia - Nadhirah Syafiqah Suhaimi; Csaba Székely; Kálmán Molnár; Gábor Cech; Boglárka Sellyei; Muhammad Hafiz Borkhanuddin (Scientific Reports)
Abstract Up to this time, only five myxosporean species have been documented from fishes of the Barbonymus genus. Due to a limited number of myxozoan studies conducted in Southeast Asia, particularly in Malaysia, the diversity of this parasite group remains largely undiscovered. In this study, a comprehensive parasitology survey was conducted, revealing nine myxozoan parasites, including five different Myxobolus spp., three Thelohanellus sp. and one Myxidium sp. Using morphological and molecular data, we describe here five new species: Myxobolus gonionoti n. sp., found in the gill filaments; Myxobolus barbonymi n. sp., and Myxobolus faizahae n. sp. found in the muscle cells; Thelohanellus gonionoti n. sp. found in the fins; and Thelohanellus barbonymi n. sp. found in the gill arches. Additionally, we identified spores of the previously described Myxobolus dykovae in the gill lamellae of B. schwanefeldii and Thelohanellus zahrahae in the gill filaments of B. gonionotus. Furthermore, two undescribed species were documented solely based on morphology and morphometrics, a Myxobolus sp. from the muscle cells of B. schwanefeldii and a Myxidium sp. from the gallbladder of B. gonionotus.